2020
DOI: 10.3389/fped.2020.559389
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Model Identifies Eosinophilic Frequencies to Powerfully Discriminate Kawasaki Disease From Febrile Infections

Abstract: Background: Kawasaki disease (KD) is a form of systemic vasculitis that occurs primarily in children under the age of 5 years old. No single laboratory data can currently distinguish KD from other febrile infection diseases. The purpose of this study was to establish a laboratory data model that can differentiate between KD and other febrile diseases caused by an infection in order to prevent coronary artery complications in KD.Methods: This study consisted of a total of 800 children (249 KD and 551 age- and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Eosinopenia appears to be a notable shared feature between MIS-C and COVID-19 52 , but not KD. These findings are consistent with the fact that KD is known to present with higher (not lower) eosinophil counts, Th2 cytokines IL-4, IL-5, and eosinophil cationic protein (ECP) [53][54][55][56][57] . As in the case of thrombocytopenia, persistent eosinopenia after admission correlated with COVID-19 severity and low rates of recovery 58 .…”
Section: Integrated Analyses Of Vip/svip Signatures Cytokine Profile and Clinical Laboratory Parameters Reveal Unique Features Of Mis-c Asupporting
confidence: 84%
“…Eosinopenia appears to be a notable shared feature between MIS-C and COVID-19 52 , but not KD. These findings are consistent with the fact that KD is known to present with higher (not lower) eosinophil counts, Th2 cytokines IL-4, IL-5, and eosinophil cationic protein (ECP) [53][54][55][56][57] . As in the case of thrombocytopenia, persistent eosinopenia after admission correlated with COVID-19 severity and low rates of recovery 58 .…”
Section: Integrated Analyses Of Vip/svip Signatures Cytokine Profile and Clinical Laboratory Parameters Reveal Unique Features Of Mis-c Asupporting
confidence: 84%
“…Other groups have also developed laboratory-only diagnostic models for KD, with a sensitivity and specificity of around 75–85% and 60–81%, respectively [ 16 , 59 , 60 ]. Our previous findings also showed that eosinophilia would be a vital predictive factor for patients with KD [ 33 , 61 ] and was associated with the failure of IVIG administration and coronary arterial formation [ 38 , 62 ]. Meanwhile, it was shown that higher procalcitonin levels occur in KD than in COVID-19 children [ 63 ] and septic children [ 18 ].…”
Section: Discussionmentioning
confidence: 91%
“…Chen et al reported that sonographic gallbladder abnormalities were associated with higher C-reactive protein, GPT, neutrophil, and IVIG resistance in KD [15]. Liu et al reported that alanine transaminase (GPT) was a major factor in the nomogram model and had high precision for distinguishing KD from fever controls [16]. The aminotransferase (AST)/ALT ratio and ALT levels in KD were reported to be significantly associated with disease severity, IVIG resistance, and CAL formation [17,18].…”
Section: Discussionmentioning
confidence: 99%